Cutaneous pseudolymphoma successfully treated with intralesional triamcinolone acetonide: A case report - Nicole Asamoah; Lara Gunton (SAGE Open Medical Case Reports)
Cutaneous pseudolymphoma refers to a group of skin conditions that simulate lymphoma either clinically and/or histologically. Cutaneous pseudolymphoma is a benign disorder that can often be misdiagnosed and has a wide range of treatment modalities. Currently, there is no gold standard of treatment, and the literature would benefit from more reports on successful and unsuccessful treatments of cutaneous pseudolymphoma. In this case, we present a 24-year-old female with cutaneous pseudolymphoma successfully treated with intralesional triamcinolone acetonide after misdiagnosis and several failures with other treatments.